DESAIN DAN IMPLEMENTASI SISTEM INFORMASI PENGAJUAN JABATAN FUNGSIONAL AKADEMIK DOSEN BERBASIS WEB PADA STMIK PPKIA PRADNYA PARAMITA MALANG - Firdaus, Nasrul; Andoko, Banni Satria; Sophia, Evy (DINAMIKA DOTCOM, 2014)
Grade of estimation credit is process to estimate achievement of lecture which is taken from activity which done based on orientation grade of estimate credit functional position of lecture.STMIK PPKIA PRADNYA PARAMITA MALANG is university in area Technology Information, but in that institute doesnât has information system which available submission increment functional position of lecture. So divicy which handle that personel division administration often difficulty to arrange and manage data submission increment functional position of lecture, so that prove with still often finded late in aggregation grade of estimation of lecture and hard which experience personal division to search file submission increment functional position of lecture.Goal from this research is a plan of information system which can handle data documentation submission increment functional position of lecture and search of data lecture which submit increment functional position of lecture so to hope this information system become one of the way to personal division to arrange and manage data functional position of lecture.Â Key Words: Â Information System, functional position of lecture, personal Division of lecture.